Labor Analgesia: Neuroaxial Approach and Maternal Satisfaction - Teixeira, Sofia Gonçalves; Santos, Alice (Journal of the Portuguese Society of Anesthesiology, 2017)
Introduction: The labor causes severe pain and maternal suffering, therefore the pregnant request is enough for neuroaxial analgesia initiation. There have been new technologies to administrate the epidural drugs during the analgesia maintenance. This can be performed by continuous epidural infusion (CEI), manuals intermittent bolus, programmed intermittent epidural bolus (PIEB), patient-controlled epidural analgesia (PCEA) or computer-integrated PCEA (CI-PCEA). The comparison of the several options as well as understand of their advantages seems of major importance. The maternal satisfaction is multifactorial and its evaluation reveals a hard task. One of the evolved factors is analgesic quality and for improve the provided services it is necessary to clarify its contribution and know other factors. Aim: This article intended to be a revision of the recent literature of neuroaxial analgesia in labor, namely analgesia maintenance and maternal satisfaction. Material and Methods: This review was based in bibliography which addresses this theme, published in the last 5 years in the databases PubMed, Web of Science and Scopus. Results: It is thought that there is no advantage in regularly use of the combined technique in relation to epidural at low dose, in regard to labor analgesia initiation. The PIEB allows a better diffusion of analgesic solution in the epidural space than CEI, resulting in less drugs consumption and pain events. The PCEA provides autonomy to the pregnant and can be used with or without a basal infusion or even associated with PIEB. This last combination presents better results, with lower pain scores and less workload to the anesthesiologist. The maternal involvement in the decision process, the relation of the pregnant with the caregivers, support from health professionals and personal expectations are important factors to the maternal satisfaction. The PIEB technique decreases the pain events and the PCEA provides autonomy, and both are associated to more satisfaction. Discussion and Conclusion: In recent years, there have been technological developments in analgesia maintenance of labor analgesia, by epidural, taking into account the maternal comfort and satisfaction. However, prospective well formulated studies are needed to conclude which scheme provides better analgesia, as well as to evaluate the maternal satisfaction with the labor experience.